Harmony in Islamic Worship across Organizational Differences: A Case Study of Nahdlatul Ulama, Persatuan Islam, and Muhammadiyah in Coba Cluster, Indonesia - Prawiyogi, Anggy Giri; Rusmana, Dadan (Jurnal Ilmiah Iqra', 2025)
TThis study aims to analyze the level of consistency in worship harmony among Muslims from Nahdlatul Ulama (NU), Persatuan Islam (Persis), and Muhammadiyah residing in the same housing complex. This research was conducted in the Koba Cluster, a residential neighborhood in Purwakarta, using qualitative methods with a case study approach. Using participatory observation and in-depth interviews, this research reveals daily religious practices, values adopted, and challenges faced in maintaining harmony. The results show that despite differences in spiritual understanding and practice, tolerance and mutual respect remain strong between the two groups. However, some challenges need to be overcome, such as differences in the interpretation of religious teachings and external influences. This research makes a significant contribution to understanding religious harmony at the micro level, as well as implications for efforts to foster a harmonious society.